2013
DOI: 10.1136/bmjopen-2013-003451
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the urgent care telephone service NHS 111 pilot sites: a controlled before and after study

Abstract: ObjectivesTo measure the impact of the urgent care telephone service NHS 111 on the emergency and urgent care system.DesignControlled before and after study using routine data.SettingFour pilot sites and three control sites covering a total population of 3.6 million in England, UK.Participants and dataRoutine data on 36 months of use of emergency ambulance service calls and incidents, emergency department attendances, urgent care contacts (general practice (GP) out of hours, walk in and urgent care centres) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 8 publications
2
119
2
2
Order By: Relevance
“…With the exception of one US study 109 that assessed impact on both ED attendances and primary care activity, only the UK-based studies of NHS Direct 66 and NHS 111 105 have attempted to assess the impact of telephone services on multiple services within the emergency and urgent care system. Whole-system impact is a key outcome if one objective of telephone-based services is to contribute to improving system efficiency.…”
Section: Telephone Triage and Advice Servicesmentioning
confidence: 99%
See 4 more Smart Citations
“…With the exception of one US study 109 that assessed impact on both ED attendances and primary care activity, only the UK-based studies of NHS Direct 66 and NHS 111 105 have attempted to assess the impact of telephone services on multiple services within the emergency and urgent care system. Whole-system impact is a key outcome if one objective of telephone-based services is to contribute to improving system efficiency.…”
Section: Telephone Triage and Advice Servicesmentioning
confidence: 99%
“…114 The evaluation of NHS 111 pilot sites found no impact on attendances at EDs and contacts with urgent primary care services but a statistically significant increase in ambulance incidents. 105 Five studies found that the introduction of a telephone advice service for low-urgency ambulance service patients resulted in fewer ambulance responses being required. 99,[101][102][103]112 However, some studies reported high call-return rates, where calls are passed back for an ambulance response, or that not as many calls as expected could be resolved by telephone.…”
Section: Service Impactsmentioning
confidence: 99%
See 3 more Smart Citations